Stereopsis and Eye Movement Abnormalities in Parkinson’s Disease and Their Clinical Implications - Ba, Fang; Sang, Tina T.; He, Wenjing; Fatehi, Jaleh; Mostofi, Emanuel; Zheng, Bin (Frontiers in Aging Neuroscience, 2022)
Background: Parkinson's disease (PD) is not exclusively a motor disorder. Among non-motor features, PD patients possess sensory visual dysfunctions. Depth perception and oculomotor deficits can significantly impact patients' motor performance. Studying stereopsis and eye behaviors using 3D stimuli may help determine their implications in disease status. Objective: The objective of the study is to investigate stereopsis and eye movement abnormalities in PD with reliable tools, and the correlation with indicators of PD severity. We hypothesize that PD patients exhibit different eye behaviors and that these differences may correlate to the severity of motor symptoms and cognitive status. Methods: Control and PD participants were first evaluated for visual acuity, visual field, contrast acuity, and stereo perception with 2D and Titmus stereotests, followed by the assessment with the 3D active shutter system. Eye movement behaviors were assessed by a Tobii X2-60 eye tracker. Results: Screening visual tests did not reveal any differences between PD and control group. With the 3D active shutter system, PD group demonstrated significantly worse stereopsis. Preserved cognitive function correlated to more intact stereo function. PD patients had longer visual response times, with a higher number of fixations and bigger saccade amplitude, suggesting fixation stabilization difficulties. Such changes showed a positive correlation with severity of motor symptoms and negative correlation with normal cognitive status. Conclusion: We assessed stereopsis with a 3D active shutter system and oculomotor behaviors with Tobii eye tracker. PD patients exhibit poorer stereopsis and impaired oculomotor behaviors during response time. These deficits correlated with PD motor and cognitive status. The visual parameters may potentially serve as clinical biomarkers for PD.